STRESS STATUS OF PATIENTS BEFORE AND AFTER SURGERY AT VINMEC TIMES CITY INTERNATIONAL GENERAL HOSPITAL IN 2022 AND SOME RELATED FACTORS (Vietnam Journal of Community Medicine, 2024)
Background: Patient psychology before and after surgery should be concerned because it closelyaffects the treatment process and the patient’s ability to recover after surgery.Objectives: Determining the stress status of patients before and after surgery at Vinmec Times CityInternational General Hospital in 2022 and some related factors.Methods: Cross-sectional survey, quantitative research.Results: The study collected information from 400 patients before and after surgery at VinmecTimes City International General Hospital through a questionnaire. The study results showed that therate of patients feeling stressed before surgery was 1,8%, of which 94,5% of patients with everydaystress, 3,8% mild stress, 1,0% moderate stress, 0,3% severe stress and 0,5% very severe stress. Aftersurgery, none of the patients were stressed. Three factors related to patient’s stress include economicdependence, time of surgery and patient’s knowledge about surgery (p
Keywords: Stress, patients before and after surgery, related factors.